Teaching and learning mathematics using digital games in the classroom - Otero, Maria Rita (2024)
The Digital Game-Based Learning (DGBL) approach was adopted, and a didactic sequence based on the digital game Triângulo Resgate (Rescue Triangle) was designed and implemented in a public secondary school course in Argentina to teach the metric relationships of the right triangle. The activities of the students and the teacher in each task of the sequence were described and analyzed. The results indicate that the game promotes the active participation of all students in classes, who use, justify, and apply the similarity of triangles and the metric relationships of the right triangle to new situations they create.